Eye movements during Chinese reading. (11th April 2013) - Liversedge, Simon P.; Hyönä, Jukka; Rayner, Keith
Abstract : Chinese written language is different from alphabetic written languages in many respects, and for this reason, interest in the nature of the cognitive processes underlying Chinese reading has flourished over recent years. A number of researchers have used eye movement methodology as a measure of on‐line processing to understand more about cognitive processing during Chinese text comprehension. This Special Issue focuses on current eye movement research investigating Chinese reading and this paper provides a brief background to this research area and a concise overview of the papers that appear in the Special Issue.